Membangun Smart City di Indonesia Tantangan dan Peluang: Studi Kasus di Kota Bada Aceh - Nasir; Yuslinaini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The development of the Smart City concept has become the main focus for many cities throughout the world, including in Indonesia. The city of Banda Aceh, as one of the important cities in Indonesia, also faces challenges and opportunities in realizing this vision. One of the main challenges faced is the lack of adequate technological infrastructure. This hampers the implementation of various Smart City services such as smart transportation systems and technology-based waste management. Apart from that, the low quality of telecommunications services also affects the growth of the digital economic sector in this city. However, there are significant opportunities to overcome these challenges. The use of technological innovations such as the Internet of Things (IoT) can be an effective solution. Collaboration between the public, private and community sectors is also key in facing these challenges. There is a need to increase investment in technological infrastructure and increase public awareness of the importance of the Smart City concept. By overcoming challenges and taking advantage of existing opportunities, the City of Banda Aceh can progress in realizing the vision of a Smart City that is inclusive, sustainable and highly competitive. This will provide great benefits for city residents in improving the quality of life and sustainable economic growth.